A Small, Stateless Nation in the World Market for Book Translations: The Politics and Policies of the Flemish Literature Fund - McMartin, Jack (TTR, 2019)
This paper discusses the Flemish Literature Fund (FLF), an autonomous government organisation created in 1999 by the Flemish Community to support Flemish literature at home and abroad. It traces the institutional history of the FLF, situating the organisation in the context of Flanders’ longstanding struggle for cultural autonomy within the Belgian state on the one hand and its strong but unequal ties to the Netherlands on the other. Using a translation sociological analytical framework, it goes on to argue that the FLF’s outgoing translation grant decisions reflect two strategies of international dissemination: a focus on the central languages of English, German and French, and a strategic use of the picture book genre to break into emerging languages on the periphery, especially Chinese. While the case of the FLF clearly illustrates the shifting power relations between state and market agents in the era of globalisation, it also indicates a novel approach to state-supported literary export designed to maximise a small, stateless nation’s international resonance in a world market for translations dominated by larger (nation-) states and languages.